G396(P) Is infantile laryngomalacia associated with early onset adenotonsillar hypertrophy: a retrospective pilot study. (27th April 2015) - Murphy, LA; Tan, SC; Wickham, M; Clements, A; Kubba, H
Abstract : Introduction: Laryngomalacia has been associated with gastroesophageal reflux (GOR), which may cause adenotonsillar hypertrophy leading to early onset obstructive sleep apnoea (OSA). We aim to assess this proposed relationship, with adenoidectomy <4 years as our primary endpoint. Method: 78 children seen in the airway clinic at the Glasgow Royal Hospital for Sick Children during September 2009 to August 2010 with a diagnosis of infantile laryngomalacia and for whom four years of follow up data was available were included, and their medical notes analysed. Results: We found a significantly increased incidence of OSA in our cohort of 11.5%, compared to a reported population incidence of 0.7–1.8% (p = < 0.0001). The rate of adenoidectomy <4 years in this sample was 12.8%. We found that children who undergo adenoidectomy are more than 4x likely to also undergo a supraglottoplasty procedure than those who do not, 70% vs. 16.2% (p = 0.0008). Significant increase in the presence of neurodisability in the group of children who underwent an adenoidectomy was also seen, 40% vs. 2.9% (p = < 0.002). Conclusion: Outcomes following adenoidectomy +/- tonsillectomy are suggestive of adenotonsillar hypertrophy being the leading cause of OSA. Our results also support an emerging link between GORD and OSA, as although there are a number of causes of adenotonsillar hypertrophy there was little evidence to suggest that any of these patients could have developed hypertrophy due to alternative mechanisms. Children with more severe laryngomalacia appear to be at higher risk of developing sleep disordered breathing symptoms, and subsequently requiring adenoidectomy.